The (un)happiness of knowledge and the knowledge of (un)happiness: Happiness research and policies for knowledge-based economies - Engelbrecht, Hans-Juergen (My University, 2008)
This paper explores the current state and interfaces of two broad policy discourses, i.e. that of policies for knowledge-based economies (KBEs) and policy implications of happiness research, which so far have exhibited little explicit cross-referencing. I first review the state of 'mainstream' knowledge policy associated with the OECD, the related but somewhat separate literature on information society indicators, and some 'non-mainstream' knowledge policy analysis. This is followed by a brief overview of some of the major policy implications and controversies in happiness research. Next, I discuss major interfaces of the two policy discourses. They mostly concern the nexus of education, work and innovation. I also illustrate the diversity of beliefs and values about some core elements of KBEs in a group of what are usually regarded as similar countries, and advocate the use of subjective variables to capture these differences. The main argument put forward in this paper is that policies for KBEs should be informed by insights from happiness research.
Paper presented to the International Conference Policies for Happiness, June 14-17, 2007, Certosa di Pontignano, University of Siena, Italy.
Keywords: Knowledge-based economy; Knowledge policy; Happiness research; Subjective well-being; Productivity; Fields of Research::340000 Economics